2014
DOI: 10.1007/s00466-014-1080-7
|View full text |Cite
|
Sign up to set email alerts
|

Small strain elasto-plastic multiphase-field model

Abstract: A small strain plasticity model, based on the principles of continuum mechanics, is incorporated into a phasefield model for heterogeneous microstructures in polycrystalline and multiphase material systems (Nestler et al., Phys Rev 71:1-6, 2005). Thereby, the displacement field is computed by solving the local momentum balance dynamically (Spatschek et al., Phys Rev 75:1-14, 2007) using the finite difference method on a staggered grid. The elastic contribution is expressed as the linear approximation accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…It has been shown in [18] that this formulation of the internal plastic energy provides the expected dissipation formulation. We derive the elastodynamic equations by calculating the variational derivative of the energy functional (1) with respect to the displacement field u [17] …”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…It has been shown in [18] that this formulation of the internal plastic energy provides the expected dissipation formulation. We derive the elastodynamic equations by calculating the variational derivative of the energy functional (1) with respect to the displacement field u [17] …”
Section: Introductionmentioning
confidence: 95%
“…By minimization of the total system energy, the models describe the propagation of cracks [7]. Extensions of this approach to plastic effects in multiphase materials are elaborated by Schneider et al [18] and applications in ferroelectric polycrystals are shown by Abdollahi and Arias [19]. Only few approaches describe crack propagation in heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations